THE PRIMARY PRODUCTS OF LIPID PEROXIDATION IN DIFFERENT FUNCTIONAL ACTIVITY OF SKELETAL MUSCLES IN COMBINATION WITH CHANGES IN PHOTOPERIOD - Hilmutdinova, M.Sh.; Cherno, V.S.; Kosharniy, V.V. (World of Medicine and Biology, 2018)
The article considers the features of the influence of immobilization stress and excessive physical activity in combination with photoperiod changes on the level of primary products of lipid peroxidation. It is shown that the combination of immobilization stress with 24-hour lighting, excessive physical activity with 24-hour lighting, as well as excessive physical activity with light deprivation increases the level of primary products of lipid peroxidation, which may indicate the strengthening of peroxidation processes. The results can be considered as a kind of adaptive response in the conditions under study.
Keywords: lipid peroxidation; immobilization stress; excessive physical activity